2019
DOI: 10.1111/csp2.90
|View full text |Cite
|
Sign up to set email alerts
|

Making structured decisions for reintroduced populations in the face of uncertainty

Abstract: Structured decision-making (SDM) has become popular in natural resource management but has been underused in reintroduction programs. We illustrate how conservation managers can use SDM to guide management decisions after initial reintroduction, when data are still limited and uncertainty around vital rates estimates is high. In 2013, the hihi (Notiomystis cincta), an endangered New Zealand forest bird, was reintroduced to Bushy Park (BP), a managed conservation reserve. High post-release mortality in females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Firstly, by applying a novel Bayesian multi-stage nest survival model, we provide insights into nest survival. Estimates of demographic parameters such as nest survival are of vital importance when making structured decisions on conservation management (including translocations) in the face of uncertainty (Panfylova et al, 2019). For wide-ranging species such as petrels, nest survival, not juvenile or adult survival, will be the likely driver of translocation success, making nest survival estimates crucial for projecting future population trajectories at translocation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, by applying a novel Bayesian multi-stage nest survival model, we provide insights into nest survival. Estimates of demographic parameters such as nest survival are of vital importance when making structured decisions on conservation management (including translocations) in the face of uncertainty (Panfylova et al, 2019). For wide-ranging species such as petrels, nest survival, not juvenile or adult survival, will be the likely driver of translocation success, making nest survival estimates crucial for projecting future population trajectories at translocation sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulation approach provides a vital tool for planning the management and conservation of a threatened long-lived population and for making objective decisions regarding trade-offs in future reintroduction projects (Converse et al, 2013;Lloyd et al, 2019;Panfylova, Ewen & Armstrong, 2019). Quantitative modeling provides explicit predictions about future population trends and the uncertainty surrounding forecast population trajectories under different extraction regimes and allows the pros and cons of different removal alternatives to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The search for innovative and effective methods to improve and optimize species conservation programs is a key issue for managers, conservationists and policy-makers responding to biodiversity loss. The translocation of individuals to formerly occupied habitats is a widespread and increasingly used tool in conservation programs to restore wild populations of endangered species (Seddon, Armstrong & Maloney, 2007;P erez et al, 2012;Seddon et al, 2014;Brichieri-Colombi & Moehrenschlager, 2016;Swan, Lloyd & Moehrenschlager, 2018). Because the economic and time costs of population replenishment and reintroduction projects can be limiting factors (Smith et al, 2011), reliable assessments of the effectiveness of various management options are essential in choosing the best course of action (McCarthy, Armstrong & Runge, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Others have analysed some components of risk (e.g. fiscal risk, risk to the target, overall uncertainty) within decision frameworks (Canessa, 2015; Panfylova et al., 2019; Rout et al., 2013). However, in looking at managed relocation from a Federal decision process perspective, we concluded that there are times and places where a broader spectrum of risk needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%